Victor Hehn en 1851 : un philologue de Dorpat et la haute police russe - Zeltchenko, Vsevolod (Hyperboreus, 2016)
The article uses archival records to trace the imprisonment of the Dorpat philologist Victor Hehn, who was soon to become a prominent student of antiquity and an Indo-Europeanist. Arrested in 1851 for maintaining a moderately liberal correspondence with baroness Méry von Bruiningk, Hehn unwittingly became entangled in a complex political and administrative scheme devised mainly to mitigate the effects of the 1848 Revolution on the professors and students of Dorpat University. This event proved to be pivotal both to Hehn’s life and his academic career.